Penerapan Pembelajaran Multikultural Dalam Lingkup Pendidikan Di Sekolah - Julia Kartika Putri (JPG: Jurnal Pendidikan Guru, 2023)
This study aims to determine the meaning of multicultural education and education and the application of multicultural learning. This type of research is literature research by collecting data in the form of books or journals that are on the topic. This research uses analytical methods with a descriptive presentation. The results showed that: (1) Education as an interaction between educators and students, (2) the concept of multicultural education in schools, (3) the application of multicultural learning in schools that makes teachers an important role in building the cultural values of students. Multicultural learning in schools can be started by holding activities, such as multicultural training, workshops, and seminars involving teaching staff, counselors, staff, and students.